Prognostic and diagnostic significance of the cardiac biomarker NT-proBNP in the perioperative period of vascular surgery procedures - I. A. Kozlov; D. A. Sokolov; P. A. Lyuboshevsky (Вестник анестезиологии и реаниматологии, 2023)
The objective was to study the dynamics of NT-proBNP blood level during the perioperative period of vascular surgery and to study the association of this biomarker level at the stages of treatment with developed cardiovascular complications (CVC).Materials and Methods. The study involved 129 patients aged 66 [61–70] years who underwent elective vascular surgery. NT-proBNP blood level was determined at stages: I – before surgery, II – 24 hours after surgery, III – before discharge from the hospital. Correlation analysis, logistic regression and ROC-analysis were used for data processing.Results. Median NT-proBNP (pg/ml) at stage I was 54[42–215], stage II – 149[63–298] (p1–2 = 0.0001) and stage III – 78[48–288] (p1–3 = 0.037). NT-proBNP blood level at stage I correlated with the biomarker level at stages II (rho = 0.558, p < 0.0001) and III (rho = 0.689, p < 0.0001). The biomarker was associated with CVC at all stages: I – OR 1.0048, 95% CI 1.0021–1.0074, p < 0.0001, AUC 0.825; II – OR 1.0040, 95% CI 1.0020–1.0060, p < 0.0001, AUC 0.820; III – OR 1.0026, 95% CI 1.006–1.0046, p = 0.015, AUC 0.687. At stage I, NT-proBNP > 218 pg/ml was a CVC predictor (sensitivity 82%, specificity 85%), this biomarker level was registered in 30 (23.2%) patients; at stage II, NT-proBNP > 281 pg/ml was associated with CVR (sensitivity 81%, specificity 80%), at stage III NT-proBNP > 158 pg/ml was associated with CCC (sensitivity 79%, specificity 65%).Conclusions. After vascular surgery, the median NT-proBNP value increases significantly, remaining within the reference limits, and does not de[1]crease until the patients discharge from the hospital. The perioperative NT-proBNP dynamics may differ in patients with different initial biomarker levels. In 23.2% of vascular surgical patients, the preoperative NT-proBNP blood level increased to a level of more than 218 pg/ml, indicating CVC risk (very good quality predictor model). After surgery, the level of NT-proBNP associated with CVC (very good quality model) exceeds 281 pg/ml. Prior to discharge of patients from the hospital, the association of NT-proBNP with CVC is characterized by a moderate quality model (AUC 0.687). The prognostic significance of the biomarker at this stage of surgical treatment needs further research.